Subacute Sclerosing Panencephalitis (Bangladesh Journal of Medical Science, 2013)
Subacute sclerosing panencephalitis (SSPE) is a rare,invariably fatal degenerative disease of central nervous system developing after measles infection.Neurological symptoms are initial presenting symtoms but rere reports of pure psychiatric symtoms preceding neurological symtoms have been reported..We here report a case of  18 years old male patient suffering from Subacute sclerosing panencephalitis (SSPE) who initially had behavioural changes and then subseqently devloped neurological symptoms.Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 344-345 DOI: http://dx.doi.org/10.3329/bjms.v12i3.12745